Numerical Investigation of the Interacted Behavior of Embankment-Slope System Under Seismic Loading Conditions - Akbay Arama, Zülal; Akın, Muhammed Selahaddin; Dalyan, İlknur; GENÇDAL, HAZAL BERRAK (Springer Nature, 2024)
In this study, the integrated effects of the geometrical characteristics of slope and the geotechnical strength properties of clayey foundation soils are investigated, considering the relative distance of the embankment from the slope edge under dynamic loading conditions with performing numerical analysis. In this context, a finite-element-based two-dimensional commercial software is used to perform pseudo-static analysis concerning the consideration of the Samos-İzmir earthquake in October 2020. The outcomes of the studies were evaluated in terms of the determining factor of safety values to interpret the effects of the envisaged variants on stability. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
Recent Research on Geotechnical Engineering, Remote Sensing, Geophysics and Earthquake Seismology
Keywords: Embankment; Finite Element Analysis; Samos-İzmir Earthquake; Slope Stability